2018
DOI: 10.1016/j.socscimed.2018.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Does the sex ratio at sexual maturity affect men's later-life mortality risks? Evidence from historical China

Abstract: This study examines the relationship between the male-to-female sex ratio (measured as the proportion male) at sexual maturity and later-life mortality risks in the context of pre-industrial northeast China, using registration data from the Qing Dynasty. We find that a higher male-to-female sex ratio at sexual maturity is associated with a higher later-life mortality risk among men. This association is likely due to the long-term adverse consequences of stress caused by low mate availability at sexual maturity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Studies have found a positive association between sex ratios at sexual maturity and later‐life mortality risk among men, which is consistent with the homeostatic principle (Jin et al. 2010; Zang and Zheng 2018). However, sex differences in mortality below the reproductive ages are small, even in a newly industrialized country like China.…”
Section: Hypothesessupporting
confidence: 73%
“…Studies have found a positive association between sex ratios at sexual maturity and later‐life mortality risk among men, which is consistent with the homeostatic principle (Jin et al. 2010; Zang and Zheng 2018). However, sex differences in mortality below the reproductive ages are small, even in a newly industrialized country like China.…”
Section: Hypothesessupporting
confidence: 73%
“…They hypothesized that Black individuals were less affected by lack of mate availability because of the well-known extreme dearth of available Black males, and they, therefore, blamed the lack of opportunity as "systemically rooted" and did not take it personally that they lacked options. Another study looked at how a skewed sex ratio with more males than females affected Chinese men and found that Chinese provinces that had fewer women, and thereby lower mate opportunities for males, were associated with higher male mortality rates (Zang & Zheng, 2018). The researchers hypothesized that increased stress because of mate competition was responsible for earlier deaths.…”
Section: Sex Ratiomentioning
confidence: 99%